Cutaneous Pseudolymphoma: A Case Report (Global Journal of Medical Research, 2023)
Objectives To report the case of a rare dermatological disease demonstrating its possible clinical and immunohistochemical variations Methods Information for carrying out the case report was communicated through medical records made available by Carapicu ba s General Hospital after approval by the institution s Ethics Committee and literature review Discussion We report the case of a 68-year-old white man retired with a history of erythematous plaques and with a very itchy scalp for 6 months Having the clinical suspicion that a cutaneous lymphoma may be involved an incisional biopsy was performed Histopathological analysis and subsequent immunohistochemistry showed polyclonal lymphoid dermal infiltrate and the diagnosis of cutaneous lymphocytoma or the most common subtype of pseudolymphoma was concluded
Keywords: cutaneous pseudolinfoma lymphoid hyperplasia lymphocytoma